Ketahanan Pangan Sebagai Pilar Kedaulatan Bangsa Dalam Perspektif Hadis Nabi - Parluhutan Siregar; Maimun; Muhadditsir Rifa'i; Khoirotul Fauziyah; Ahmad Farhan (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Food security constitutes a fundamental pillar of national sovereignty, as it determines a nation’s capacity to ensure the welfare, stability, and independence of its people. In contemporary contexts, challenges such as climate change, rapid urbanization, economic inequality, and dependence on global markets increasingly threaten the sustainability of food systems, particularly in developing countries. Within Islamic teachings, food security is not merely an economic or technical concern but an ethical and spiritual responsibility rooted in prophetic guidance. This study examines the concept of food security from the perspective of the Prophetic Hadith of Muhammad PBUH, emphasizing its relevance to national sovereignty and social justice. Employing a qualitative library-based research method, this study analyzes selected hadiths related to agricultural productivity, equitable resource distribution, the prohibition of hoarding, environmental stewardship, and the obligation to uphold human dignity. Through thematic and normative analysis, the findings reveal that the Prophet Muhammad promoted food security as a collective responsibility involving individuals, communities, and governing authorities. The prophetic traditions underscore principles of sustainability, fairness, and social solidarity as essential foundations for resilient food systems. The study demonstrates that the Hadith provides a comprehensive ethical framework that supports national sovereignty by strengthening domestic food production, ensuring equitable access to nutritious food, and preventing structural injustice in food distribution. Therefore, integrating prophetic ethical values into contemporary food policies can enhance national resilience and sovereignty while advancing sustainable development, reaffirming the continuing relevance of the Prophetic Hadith in addressing modern food security challenges.